NURSING ANALYSIS OF STROKE PATIENTS WITH PHYSICAL MOBILITY DISORDERS PROBLEMS WITH RANGE OF MOTION EXERCISE INTERVENTIONS IN GARDENA ROOM RSD DR. SOEBANDI JEMBER - Widya Maulina Cantika Putri; Ruris Haristiani (International Journal of Biomedical Nursing Review, 2025)
Introduction: Blooding in the brain leads to inadequate supply within the brain, resulting in an infarction of the cerebral tissue, which affects the surrounding nerves, leading to a loss of muscle strength and physical weakness. Purpose: Giving range of motion therapy after stroke provides changes in the sensory and motor cortex by improving motor function in the patient. Methods: This exercise is given once every shift with a duration of 10 to 15 minutes in 3 days, showing an increase in muscle strength and range of joint movement in the upper and lower left extremities. Discussion: Range of motion is one form of rehabilitation that is considered quite effective in preventing permanent disability in stroke patients. This exercise contains a set of movements that focus on the joints so that they can improve muscle flexibility and strength. Conclusion: By administering range of motion exercise therapy to stroke patients with physical mobility impairment, the desired outcome criteria can be achieved, namely an increase in muscle strength and range of extremity movement